2018
DOI: 10.1177/0391398818784276
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification with longitudinal neutrophil to lymphocyte ratio assessment after left ventricular assist device implantation

Abstract: Our results indicate a significant inflammatory response to implantation of the left ventricular assist device, a known effect. The magnitude of this response may be effectively and easily monitored over time using the neutrophil-to-lymphocyte ratio. In general, approximately 30 days is required for the neutrophil-to-lymphocyte ratio to return to preoperative levels. After several months, the neutrophil-to-lymphocyte ratio improves to below preoperative levels. It is possible that this reduction reflects the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Bhat et al further proved that the NLR variability in time was correlated to outcomes in HF patients receiving LVAD therapy [45]. Highest NLR levels were recorded immediately after surgery with a tendency to decrease after approximately 30 days to levels similar to the preoperative ones [45].…”
Section: Left Ventricular Assist Devicementioning
confidence: 97%
See 1 more Smart Citation
“…Bhat et al further proved that the NLR variability in time was correlated to outcomes in HF patients receiving LVAD therapy [45]. Highest NLR levels were recorded immediately after surgery with a tendency to decrease after approximately 30 days to levels similar to the preoperative ones [45].…”
Section: Left Ventricular Assist Devicementioning
confidence: 97%
“…Bhat et al further proved that the NLR variability in time was correlated to outcomes in HF patients receiving LVAD therapy [45]. Highest NLR levels were recorded immediately after surgery with a tendency to decrease after approximately 30 days to levels similar to the preoperative ones [45]. However, patients whose NLR failed to improve 10 days postoperative had higher probability of a longer length of stay, of developing right HF and a trend toward reduced survival rates [45].…”
Section: Left Ventricular Assist Devicementioning
confidence: 99%
“…The preoperative NLR is typically above normal levels, and increases further postoperatively, reflecting the acute inflammatory response to surgery. However, the NLR then reduces logarithmically, reaching lower than preoperative values at 3–6 months follow-up [69–71]. Previous studies have reported that a high pre-LVAD NLR is predictive of mortality during the LVAD support period [69,72].…”
Section: Neutrophil-to-lymphocyte Ratio In Heart Failure and Heart Tr...mentioning
confidence: 99%
“…Previous studies on VAD patients reported a marked increase in neutrophil‐to‐lymphocyte ratio (NLR) by postoperative day (POD) one 8,9 . Although NLR normalized to preoperative levels by 1 month and plateaued by 3 months in some patients, 8,10 elevated levels at 3–6 months post‐implantation were associated with higher rates of stroke and mortality 9,10 . Another study of 20 patients showed an increase in MAC‐1 expression (i.e., activated neutrophils) postoperatively with sustained elevation even up to 30–60 days depending on VAD type 11 .…”
Section: Introductionmentioning
confidence: 98%
“…There is limited literature on the changes that occur to neutrophils under in vivo conditions in patients with implanted CF‐VADs. Previous studies on VAD patients reported a marked increase in neutrophil‐to‐lymphocyte ratio (NLR) by postoperative day (POD) one 8,9 . Although NLR normalized to preoperative levels by 1 month and plateaued by 3 months in some patients, 8,10 elevated levels at 3–6 months post‐implantation were associated with higher rates of stroke and mortality 9,10 .…”
Section: Introductionmentioning
confidence: 99%